Factors Affecting Teachers’ Technological Methodologies, Practices and Teaching Performance: A Descriptive Analysis (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of this study is to identify and describe the factors affecting teachers’ technological methodologies, practices, and teachers’ teaching performance in Baliwasan Senior High School- Stand-Alone this school year 2020-2021. The study employs a checklist to determine the quantitative outcome of the given data. The findings revealed that factors affecting technological methodologies in terms of resources, teachers’ experience with ICT, and teaching strategies were highly affected and at a high level for digital resources, online classes, and ICT integrations. In contrast, the results for internet connection and ICT integration were moderately affected and at a moderate level, respectively.